2017
DOI: 10.3390/ijms19010048
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Catabolite Repression in Filamentous Fungi

Abstract: Carbon Catabolite Repression (CCR) has fascinated scientists and researchers around the globe for the past few decades. This important mechanism allows preferential utilization of an energy-efficient and readily available carbon source over relatively less easily accessible carbon sources. This mechanism helps microorganisms to obtain maximum amount of glucose in order to keep pace with their metabolism. Microorganisms assimilate glucose and highly favorable sugars before switching to less-favored sources of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 211 publications
(303 reference statements)
5
143
0
5
Order By: Relevance
“…Transcription factor CreA and catabolic pathways involved in less favorable carbon sources of P. radiata were not induced under hypoxia. Therefore, we concluded that concentration of glucose or other carbohydrates was not high enough to induce carbon catabolite repression [51] under hypoxia. Expression of the diauxic shift-associated transcription factor Cat8 candidate in P. radiata [37] followed a similar pattern to CreA.…”
Section: Adaptation To Hypoxia By Regulation Of Intracellular Metabolismmentioning
confidence: 89%
“…Transcription factor CreA and catabolic pathways involved in less favorable carbon sources of P. radiata were not induced under hypoxia. Therefore, we concluded that concentration of glucose or other carbohydrates was not high enough to induce carbon catabolite repression [51] under hypoxia. Expression of the diauxic shift-associated transcription factor Cat8 candidate in P. radiata [37] followed a similar pattern to CreA.…”
Section: Adaptation To Hypoxia By Regulation Of Intracellular Metabolismmentioning
confidence: 89%
“…It is important to note that cellulases and most of the plant cell-wall hydrolyzing enzymes are inducible and are also influenced by catabolite repression in many fungi (Adnan et al, 2017). The decline of endoglucanase activity after the maximum peak of enzyme secretion could be attributed to cumulative release of cellobiose at the start of the hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…The same repressor has been proved to influence the synthesis of lignolytic enzymes (Janusz et al, 2013), cellulases (Bischof et al, 2016), and hemicellulases (Amore et al, 2013). Moreover, it may also affect fungal growth, virulence, morphology, and utilisation of nonglucose sources (Adnan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%